Do Meio à Classe Média: como a “nova classe média” e a “classe média tradicional” percebem sua posição social? - André Salata; Celi Scalon (Ciências Sociais Unisinos)
The paper aims to bring new elements to the current debate about the middle class in Brazil, taking the class identities and perceptions about middle class as its object. In recent years a huge number of individuals and families achieved intermediate levels of income and joined the middle layer of the population. We analyze the perceptions of those individuals about their social position – seeking to establish a comparison with the perception present among the “traditional middle class” – using data collected through semi-structured interviews. The analyzes show that individuals of intermediate socioeconomic profile do not seem to be the ones who more typically identify themselves as middle class; it was only among respondents of “traditional middle class” that we observed a clear and obvious identification with that class. These results show some of the limitations of the concept of ‘new middle class’ currently applied to Brazil.